Environmentally Friendly Port Management Based on Optimum Role Model - Amrullah, Romanda Annas; Imanto, Frankie; Arleen, Arleen; Rahkman, Rizqi Aini (Indonesian Research Journal on Education, 2024)
The port is a gateway for a country to enter and exit production goods from all over the world. However, the existing port is still not environmentally friendly as expected. This study uses a research journal method with the results of the concept of a new model. The indicators of the model concept are discussed along with the advantages and disadvantages that may be faced during field trials. Optimum role model is the attitude of a leader who is able to be a role model by implementing digitalization, paperless, having high and special skills and supported by the right description to achieve work efficiency.